Challenges and opportunities for omics-based precision medicine in chronic low back pain - Firdous, Ayesha; Gopalakrishnan, Vanathi; Vo, Nam; Sowa, Gwendolyn (European spine journal, 2025)
Purpose Chronic low back pain (cLBP) is a common health condition worldwide and a leading cause of disability with an estimated lifetime prevalence of 80–90% in industrialized countries. However, we have had limited success in treating cLBP likely due to its non-specific heterogeneous nature that goes beyond detectable anatomical changes. We propose that omics technologies as precision medicine tools are well suited to provide insight into its pathophysiology and provide diagnostic markers and therapeutic targets. Therefore, in this review, we explore the current state of omics technologies in the diagnosis and classification of cLBP. We identify factors that may serve as markers to differentiate between acute and chronic cases of low back pain (LBP). Finally, we also discuss some challenges that must be overcome to successfully apply precision medicine to the diagnosis and treatment of cLBP. Methods A literature search for the current applications of omics technologies to chronic low back pain was performed using the following search terms— “back pain,” “low back pain,” “proteomics,” “transcriptomics”, “epigenomics,” “genomics,” “omics.” We reviewed molecular markers identified from 35 studies which hold promise in providing information regarding molecular insights into cLBP. Results GWAS studies have found evidence for the role of single nucleotide polymorphisms (SNPs) associated with pain pathways in individuals with cLBP. Epigenomic modifications in patients with cLBP have been found to be enriched among genes involved in immune signaling and inflammation. Transcriptomics profiles of patients with cLBP show multiple lines of evidence for the role of inflammation in cLBP. The glycomics profiles of patients with cLBP are similar to those of patients with inflammatory conditions. Proteomics and microbiomics show promise but have limited studies currently. Conclusion Omics technologies have identified associations between inflammatory and pain pathways in the pathophysiology of cLBP. However, in order to integrate information across the range of studies, it is important for the field to identify and adopt standardized definitions of cLBP and control patients. Additionally, most papers have applied a single omics method to a sampling of cLBP patients which have yielded limited insight into the pathophysiology of cLBP. Therefore, we recommend a multi-omics approach applied to large global consortia for advancing subphenotyping and better management of cLBP, via improved identification of diagnostic markers and therapeutic targets.